2010
DOI: 10.4161/psb.5.12.13820
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged root hypoxia effects on enzymes involved in nitrogen assimilation pathway in tomato plants

Abstract: IntroductionPlants grow in a dynamic environment, which frequently imposes constraints on growth and development. Among the adverse environmental factors commonly encountered by land plants, flooding is one of the most significant abiotic stresses. 1 Flooding of the soil can have a tremendous impact on the growth and survival of plants, and thereby on agricultural as well as natural ecosystems. In the last decades considerable progress has been made in our understanding of the mechanisms that enable certain pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…− to NO 2 − (50 to 100 fold) and NR preference for NO 3 − rather than NO 2 − . However, hypoxia results in a higher accumulation of NO 2 − and therefore a higher level of NO can be produced via the NR pathway and mitochondrial cytochrome c oxidase [31][32][33] .…”
Section: Hypoxia Affects the Link Between N Metabolism And No Formatimentioning
confidence: 99%
“…− to NO 2 − (50 to 100 fold) and NR preference for NO 3 − rather than NO 2 − . However, hypoxia results in a higher accumulation of NO 2 − and therefore a higher level of NO can be produced via the NR pathway and mitochondrial cytochrome c oxidase [31][32][33] .…”
Section: Hypoxia Affects the Link Between N Metabolism And No Formatimentioning
confidence: 99%
“…Oliveira (2010) pointed out another characteristic of the enzyme to use of energy from photosynthesis, which regulates the supply of carbon skeletons for incorporation of nitrogen into amino acids. The free ammonium accumulation in plant tissue in high concentrations of NaCl may be attributed to their direct uptake, nitrate reduction, deamination of nitrogenous compounds by photorespiratory cycle or by biological fixation (Horchani and Ashi-Smiti, 2010). Several authors have shown that plants under salt stress conditions promote an increase in the activity of the enzymes glutamine synthetase (GS) and glutamate synthase (GOGAT) involved in ammonium assimilation, which are assimilated on the alternative route glutamate dehydrogenase (GDH) (Carvalho, 2012;Taiz and Zeiger, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The GS/GOGAT cycle is the principal route of ammonium assimilation in plants [ 125 ]. In tomato ( Solanum lycopersicum L.), the activity of the ATP-consuming GS was significantly enhanced in roots during prolonged root hypoxia [ 126 ]. Here, a striking contrast in the GS transcriptional pattern was evidenced between ‘Mariana 2624’ and ‘Mazzard F12/1’ roots under hypoxic conditions, as GS transcripts were strongly accumulated in the hypoxia-tolerant genotype after 24 h of waterlogging, but consistently downregulated as stress progressed in the hypoxia-sensitive one ( Figure 1 ).…”
Section: Transcriptomic Reprogramming Of Principal Pathways Involvmentioning
confidence: 99%